The Influence of Driving Factors for the Opening of Settlements on Protected Forest Areas in Nahel Hamlet, Gunung Nona, Nusaniwe District, Ambon City - Toker, Stefani; Lasaiba, Mohammad Amin; Leuwol, Ferdinand Salomo (Jurnal Pendidikan Geografi Unpatti, 2024)
The opening of settlements in the Mount Nona protected forest area is influenced by driving factors such as increasing population, housing needs, poverty and the economy, accessibility and infrastructure, government policies, lack of environmental awareness, land conflicts, and disputes. This research aims to identify the driving factors for opening settlements and determine the ecological impact on the Gunung Nona protected forest area, Nusaniwe District, Ambon City. The type of research used for this research is the combination type; the combination type is a type of research that uses more than one type of research, namely quantitative research and qualitative research. The mixed methods approach combines quantitative surveys and qualitative interviews with a sample of the community (consisting of 50 respondents). The research results show that several factors driving the opening of settlements in the Mount Nona protected forest area influence the environmental awareness factor based on the data testing results using the SPSS application. Apart from that, based on the results of interviews with the Nahel Gunung Nona Hamlet Government, the opening of settlements in the Gunung Nona protected forest area began with the diversion of displaced people from clove and red stone plantations to the city, precisely in Wainitu, because there was no more empty land to the town of Ambon, during riots. So, in this case, the Ambon city government approached the Amahusu State government and the Urimesing State government to provide land to accommodate refugees at that time. However, after the riots ended, the population became denser, so the Amahusu State government gave use rights, namely certificates, for people to build houses and live on Mount Miss; in this case, there is a protected forest area. Settlements in the Mount Nona protected forest area are increasingly growing due to the increase in population from refugee camps.